2005
DOI: 10.1081/pln-200049184
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Modified N-Expert System for Vegetable Production in the Beijing Region

Abstract: A series of field experiments were conducted over a three-year period to test a modified N-Expert system (the decision support system for nitrogen recommendations) with different irrigation regimes for a rotation of amaranth (Amaranthus tricolor L.), spinach (Spinacia oleracea L.), and cauliflower (Brassica oleracea L.). Local commercial fertilizer practice based on farmer surveys was selected as the control, and irrigation treatments followed conventional practice with a balanced irrigation schedule. Some par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For instance, N-expert, developed in Germany for growers to manage N applications (Fink and Scharpf 1993) was modified and tested by researchers in China, who found lower recommended N applications, lower residual N at harvest and no difference in marketable yield compared to conventional practices of not using N-expert (Chen et al 2005). However, it is not known if N-expert could successfully recommend the optimal rate of N.…”
Section: Plant Uptake Of Nitrogen and Crop Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, N-expert, developed in Germany for growers to manage N applications (Fink and Scharpf 1993) was modified and tested by researchers in China, who found lower recommended N applications, lower residual N at harvest and no difference in marketable yield compared to conventional practices of not using N-expert (Chen et al 2005). However, it is not known if N-expert could successfully recommend the optimal rate of N.…”
Section: Plant Uptake Of Nitrogen and Crop Productionmentioning
confidence: 99%
“…It may not be unusual for North American vegetable producers to apply over 300 kg N ha -1 in a single growing season. Moreover, based on grower surveys in Beijing Province, China, organic and inorganic N applications average from 607 to 679 kg N ha -1 for Chinese cabbage (B. campestris L.), with a maximum application of 2093 kg N ha -1 (Chen et al 2005). Clearly agronomic, economic, and environmental concerns must be addressed for the development of best management practices (BMP) that improve crop use of applied nutrients and reduce the potential losses of nutrients into the environment.…”
Section: Vegetable Cropsmentioning
confidence: 99%
“…These may contribute to large amounts of potentially leachable nitrogen in fallow period (Addiscott et al, 1991;Powlson, 1993). Additionally the plastic covers are often removed from the greenhouses and the land is often subject to excessive irrigation and large rainfall events during the summer fallow season in north China (Chen et al, 2005). Hagedorn et al (1997) showed that under heavy rains, topsoil mineral N decreased by 50-70% within the first two weeks.…”
Section: Catch Crop Use In Vegetable Production Of North Chinamentioning
confidence: 99%
“…The N inputs may include the credits listed above plus soil mineral nitrogen present in spring and N additions in precipitation, dry deposition and irrigation water. Values for each component may be region specific, but can commonly be found in the literature (Scharpf and Wehrmann 1991;Tremblay et al 2001;Chen et al 2005) and computer programs have been developed to simplify the exercise (Rahn et al 1996;Yang et al 2007). Such N budget approaches have been effective in optimizing fertilizer N management in a number of crop species (Burns 2006).…”
Section: Nitrogen Budget Approachesmentioning
confidence: 99%